Effectiveness of Web-Based “Sipamer” Application and Lecture Method in Increasing Knowledge and Early Detection of Adolescent Mental Health - Puspita Sari; M. Ridwan; La Ode Reskiaddin (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Mental illness is a health condition that causes changes in emotions, thoughts and behavior, often affecting teenagers due to psychological and hormonal changes that are not yet stable. This study aims to assess the effectiveness of using web-based applications and lecture methods in improving knowledge and the ability to self-detect mental health disorders in adolescents and first tested in the local Indonesian context. Methods: This study used a quasi-experimental design, namely two groups, namely pre-test-post-test, with purposive sampling involving 120 adolescents. The study was conducted in the Working Area of Putri Ayu Health Center, Jambi City, in two Posyandu Remaja Data collection was carried out from July to October 2024 through observation and filling out questionnaires, with data analyzed using covariance analysis. Results: Web-based application and lecture method effectively improved mental health knowledge (p<0.05). Both interventions significantly improved adolescents’ mental health self-detection scores in this group; however, the web-based application showed a greater mean increase than the lecture method. This suggests that the web-based sipamer application is more effective in improving adolescents’ mental health knowledge and self-detection skills.The advantages of the Sipamer application lie in its interactive self-screening features and expert system that facilitate early detection, making it a superior solution compared to conventional methods. Conclusion: Both the web-based application “Sipamer” and the lecture method effectively increase knowledge and self-assessment of adolescent mental health.